Perguntas como estratégias de tutoramento no ensino de leitura em português para estrangeiros - Braida, Fabrícia Cavichioli (2008)
In the last decades language specialists and researchers have dedicated special attention to the teaching of languages in general. Many of these researches have directed their interests to the analysis of textbooks, aiming as main purpose to point out improvements and/or possible modifications on them in order that they could contribute as in the structural quality of these textbooks as in their use in the classroom. Thus, trying to expand still more this field, this research aims at analyzing the textbooks used in the teaching of Portuguese as a Foreign Language. That s why, this study is guided by two general objectives: (1) investigating to what extend the questions proposed by the authors in the textbooks reading sections help both teacher and student to cross the Zone of Proximal Development; (2) comparing the modelpattern of didactic material as well as the reading sections analyzed in order to verify in which materials the teacher notice rates of improving toward what he considers appropriate to the teaching of reading. For integrating the corpus of such investigation, three student s textbooks followed by the teacher s book were selected, adding a total of six books. In these books, questions elaborated by the authors in the reading section were analyzed. For so, as the referential methodology the second generation of the Activity Theory, proposed by Leontiev (1978), was considered relevant, mainly the three hierarchical levels of activity- activityactions and operations. Then, based on the data analyses, it was possible to conclude that the questions proposed by the authors are not structurally connected with the aim of propitiating, between teacher and student, the work in Zone of Proximal Development (ZPD). Besides that, the textbooks present an inconsistent connection, some typologies are structured in a traditional way, becoming their main goal to evaluate the student in relation to the contents offered by the book and, mainly, leading him to reproduce ready knowledge. However, as opposed to the kind of questions found out in this books (for both student and teacher), there are questions elaborated in the model-pattern of the didactic materials, which are understood as a kind of tutorial strategy. Thus, they are defined due to the aid that they provide for teacher and student in order that they can work in ZPD. The growing connection of such questions enable the student of working firstly in the real development line to gradually, tutored by the teacher, advance toward the potential development line. When the teacher tutors the learner he helps this learner to consolidate more effectively the knowledge that belongs to potential development line. That is, the aid dedicated via these questions helps the foreigner learner to construct the knowledge that was not formed yet, enabling him to advance toward superior levels of development.